Micropattern-based platform as a physiologically relevant model to study epithelial morphogenesis and nephrotoxicity - Bosch-Fortea, Minerva; Rodriguez-Fraticelli, Alejo E.; Herranz, Gonzalo; Hachimi, Mariam; Barea, Maria D.; Young, Joanne; Ladoux, Benoit; Martin-Belmonte, Fernando (Biomaterials, 2019)
Tubulogenesis in epithelial organs often initiates with the acquisition of apicobasal polarity, giving rise to the formation of small lumens that expand and fuse to generate a single opened cavity. In this study, we present a micropattern-based device engineered to generate epithelial tubes through a process that recapitulates in vivo tubule morphogenesis. Interestingly, tubulogenesis in this device is dependent on microenvironmental cues such as cell confinement, extracellular matrix composition, and substrate stiffness, and our set-up specifically allows the control of these extracellular conditions. Additionally, proximal tubule cell lines growing on micropatterns express higher levels of drug transporters and are more sensitive to nephrotoxicity. These tubes display specific morphological defects that can be linked to nephrotoxicity, which would be helpful to predict potential toxicity when developing new compounds. This device, with the ability to recapitulate tube formation in vitro, has emerged as a powerful tool to study the molecular mechanisms involved in organogenesis and, by being more physiologically relevant than existing cellular models, becomes an innovative platform to conduct drug discovery assays.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Drug-development; Microenvironment; Micropatterns; Nephrotoxicity; Organ-on-achip; Tubulogenesis